Transformation Of Conventional To Digital Marketing: A Study On Increasing Sales Through Digital Marketing - Nanda Aqilah Saputri; Trisni Handayani (UNIVED Press, 2024)
The development of digital technology continues to grow along with the times. Access to the internet is another development that affects people's lives. Similarly, internet access in economic activities also contributes to the development of small and medium enterprises. Micro, Small and Medium Enterprises (MSMEs) utilize information technology in running their business. This study aims to determine the right marketing strategy at Rene Café, the ultimate goal to be achieved is to significantly increase sales and present a good company brand image to consumers. The research method used by researchers in this study is a qualitative method. This type of research is descriptive qualitative, using the methods of observation, interview, and documentation. The results showed that Rene Café has not fully optimized using all social media, but the success of Rene Café in digital marketing through social media is working with influencers or content creators and consumer reviews. By collecting data and information related to marketing through social media and the influence of an influencer in providing information about products. This shows that reviews and influencers play an important role.